Handbook of employee engagement : perspectives, issues, research and practice - Albrecht, Simon L. (Edward Elgar Publishing Ltd. CheltenhamGB, 2010)
Includes a comprehensive collection of conceptual pieces and research studies aimed at summarising from across the globe. Aims to helf researchers and practitioners identify, understand and apply the key theories, models, measures and interventions associated with employee engagement